Role of IGF-Binding Protein 3 in the Resistance of EGFR Mutant Lung Cancer Cells to EGFR-Tyrosine Kinase Inhibitors - Choi, Yun Jung (Public Library of Science, 2013)
Most patients treated with EGFR-tyrosine kinase inhibitors (EGFR-TKIs) eventually develop acquired resistance. Loss of expression of insulin-like growth factor (IGF)-binding protein-3 (IGFBP-3) has been suggested as a possible mechanism of resistance to EGFR-TKIs in the A431 and HN11 cell lines. Here, we investigated IGFBP-3 expression in two EGFR mutant lung cancer cell lines with resistance to EGFR-TKIs and examined the value of serum IGFBP-3 level as a marker of resistance. The effect of the induction or suppression of IGFBP-3 expression on resistance was also evaluated. HCC827 sublines with resistance to gefitinib (HCC827/GR) and erlotinib (HCC827/ER) were established. Loss of IGFBP-3 expression was detected by Western blotting in both cell lines without changes in transcriptional activity, and ELISA showed significantly lower amounts of secreted IGFBP-3 in the culture media of the mutant cell lines than in that of the parental line. Despite the loss of IGFBP-3 expression, IGFR signalling activity remained unchanged. Forced expression of IGFBP-3 by adenovirus-mediated transfection or recombinant IGFBP-3 slightly increased the growth-inhibitory and apoptotic effects of EGFR-TKIs, whereas suppression of IGFBP-3 did not affect sensitivity to EGFR-TKI. Serum IGFBP-3 levels measured by ELISA before and after the development of EGFR-TKI resistance in 20 patients showed no significant changes (1815.3±94.6 ng/mL before treatment vs. 1778.9±87.8 ng/mL after EGFR-TKI resistance). In summary, although IGFBP-3 downregulation is associated with the acquisition of resistance to EGFR-TKIs regardless of the mechanism, its effect on resistance was not significant, indicating that IGFBP-3 may not play an important role in resistance to EGFR-TKIs and serum IGFBP-3 level is not a reliable indicator of resistance.